Evaluating the efficacy of GIS maps as boundary objects: unpacking the limits and opportunities of Indigenous knowledge in forest and natural resource management. Issue 1 (2nd January 2022) - Shaw, Ashley; Steelman, Toddi; Bullock, Ryan
ABSTRACT: The meaningful inclusion of diverse forms of knowledge, such as Indigenous knowledge (IK), remain unrealized in many natural resource management decision-making processes. Innovative boundary objects could be used to facilitate the effective inclusion of IK in natural resource management decision-making processes. In this study, Geographic Information Systems (GIS) maps were used as boundary objects due to their ability to visually display IK across knowledge boundaries. Using a conceptual framework that combines the Six Faces of Traditional Ecological Knowledge (TEK) outlined by Houde (2007 ). "The Six Faces of Traditional Ecological Knowledge: Challenges and Opportunities for Canadian Co-Management Arrangements." Ecology and Society 12 (2): 34–50. http://www.ecologyandsociety.org/vol12/iss2/art34/ ) and boundary object criteria derived from the boundary science literature, our study investigated whether and how GIS maps could be used to increase the influence of IK on forest management. The four boundary object criteria (interpretive flexibility, accommodating concreteness, facilitating joint process, and satisfying information need) generated insight into specific ways to reduce the current barriers that may restrict greater use of IK within GIS and allow them to function more effectively as boundary objects.